2020
DOI: 10.36262/widyakala.v7i1.277
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Experiential Marketing Terhadap Loyalitas Pelanggan Ritel Di Indonesia

Abstract: The competition in retail industry becomes more dynamic and every organization need to develop new strategy to stand up in this competition. The objective of this research is to analyze the influence of experiential marketing on customer loyalty through customer satisfaction as intervening variable at retail industry in Indonesia. The research use 236 respondents as samples and collected by purposive sampling method. The obtained data then analyzed using Structural Equation Modeling (SEM) method through IBM SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 6 publications
3
8
1
5
Order By: Relevance
“…which states that the influence of Experiential Marketing is 0.173 positive and the significant value is 0.096 <0.05, meaning that the Effect of Experiential Marketing (X2) is positive but not significant on Customer Loyalty. This conclusion agrees with Karuniatama et al, (2020) which states that there is a significant positive influence of Experiential Marketing on Loyalty. However, it is different as stated by Panjaitan, (2017) which concludes that the positive relationship is also significant.…”
Section: B) the Effect Of Experiential Marketing On Customer Loyaltysupporting
confidence: 91%
See 1 more Smart Citation
“…which states that the influence of Experiential Marketing is 0.173 positive and the significant value is 0.096 <0.05, meaning that the Effect of Experiential Marketing (X2) is positive but not significant on Customer Loyalty. This conclusion agrees with Karuniatama et al, (2020) which states that there is a significant positive influence of Experiential Marketing on Loyalty. However, it is different as stated by Panjaitan, (2017) which concludes that the positive relationship is also significant.…”
Section: B) the Effect Of Experiential Marketing On Customer Loyaltysupporting
confidence: 91%
“…According to Fatmawati & Rahayu, (2018) which states that Experiential marketing consists of sense, feel, act, relate has a positive and significant effect on loyalty, while the think variable has a significant negative effect on loyalty. In contrast to the conclusion from Karuniatama et al, (2020) concluded that the effect of experiential marketing was positive but not significant on loyalty. According to Panjaitan, (2017) Research conducted states that Experiential Marketing has a positive and significant effect on loyalty.…”
Section: Introductioncontrasting
confidence: 57%
“…Sense berhubungan denganisensory experience. Sensory experience adalah usaha untuk menciptakan pengalaman yang berkait dengan panca indra melalui penglihatan, suara, sentuhan, rasa, dan bau (Karuniatama et al 2020). Menurut Rendi (2021) Feel merupakan dimensi yang berhubungan dengan affective experience.…”
Section: Tinjauan Literatur Experiential Marketingunclassified
“…Peningkatan kualitas akan menyebabkan kepuasan pelanggan. Menurut Kotler & Keller (2016) dikutip dalam Karuniatama, Barata, & Suyoto (2020) kepuasan pelanggan adalah perasaan senang atau kecewa seseorang yang dihasilkan dari membandingkan kinerja (atau hasil) suatu produk atau layanan yang diharapkan. Pengendalian kualitas dengan metode statistik merupakan metode yang dalam aktifitasnya menggunakan alat bantu statistik yang terdapat pada Statistical Quality Control (SQC) (Noor.…”
Section: Latar Belakangunclassified